Mecanismos legais e contratuais de enfrentamento de crise societária em sociedades empresárias - Chaves, João Leandro Pereira Chaves (2021)
The present work aims to bring the legal and contractual mechanisms to overcome the corporate crisis, initially addressing the formation of business companies, ways of exercising control and the emergence of corporate crises, causing the impossibility of decision making by partners and consequent paralysis of social activities performed by companies, the only alternative being the breaking of the corporate bond in relation to a partner as a way of overcoming. As for legal provisions as a mechanism to overcome the corporate crisis, the work deals with unmotivated withdrawal, motivated withdrawal, exclusion of partner and dissolution of companies, analyzing aspects and requirements, in order to make them compatible with the scenario of corporate crisis. Regarding the contractual overcoming mechanisms, the work exposes the main characteristics of the clauses for the purchase or sale of equity and the clauses for the purchase or sale option, for the purpose of highlight the necessary requirements so that the agreed terms are not subsequently invalidated, with the same result as the legal provisions, that is, a discussion before the Judiciary or Arbitral Tribunal